AN ANALYSIS ON STAGES OF ADDICTION ACCORDING TO IBN QAYYIM AL-JAWZIYYAH’S THEORY OF AL-`ISHQ - Abdul Wahab Bin Md. Ali; Abdul Wahab Bin Md. Ali; Wan Mohd Yusof Bin Wan Chik; Wan Mohd Yusof Bin Wan Chik (Journal of Islamic, Social, Economics and Development, 2024)
Addiction is a human mental condition that occurs through certain various stages. Each individuals’ craving towards certain things or objects has its own symptoms and differs according to each specific context. This area of knowledge had drawn several Islamic scholars in the past to perform in-depth research on the aspects of addiction and craving behavior. One prominent scholar, Ibn Qayyim al-Jawziyyah comprehensively discusses this issue in several of his literatures by introducing the ‘Ishq concept or theory. This research aims to find a connection between ‘Ishq theory and the stages of addiction through inductive, deductive and comparative methods. As a result, we found that there exist a strong connection between ‘Ishq theory and addiction through the definition as well as its stages. Thus, the therapy approach that was suggested by Ibn Qayyim with regards to the stages of addiction could be a good input in outlining rehabilitative measures in dealing with addiction related issues.